Legal Policy Regional Governments In The Distribution Of Social Assistance To The Affected Communities Covid-19 - Natalia Eunike Melisa; Mawuntu, J. Ronald; Setlight, Mercy M. M. (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Abstract: This study aims to analyze the regulations regarding local government policies in the distribution of Covid-19 social assistance in Indonesia. The research method used in this study includes the type of normative juridical research which includes researching and studying norms in laws and regulations, especially those relating to the object of research. Legal materials that will be studied in normative legal research are in the form of primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique used is by conducting a search through laws and regulations, and comparing it with materials regarding the fulfillment of social assistance for communities affected by Covid-19 by the Regional Government which were collected by conducting studies and inventories and then linking their contents with legal materials in the form of literature. law. The results of the study show that the regulation regarding the authority of local governments in distributing Covid-19 social assistance in Indonesia is reviewed from the first point of view, the basic rules for distributing Covid-19, namely general rules governing the source and mechanism for distributing social assistance funds as well as arrangements regarding the delegation of authority to local governments given by the central government based on the principles of decentralization and deconcentration in terms of the provision of social assistance. Second, more specific rules regarding the distribution of social assistance by provincial/district/municipal governments have been regulated in each regional regulation and each has different forms and mechanisms for distributing social assistance. Keywords: Legal Policy; Local Government; Social Assistance; Covid-19